Identification of distinct physical activity profiles through adolescence: a longitudinal qualitative description study - Bélanger, Mathieu; Goguen, Julie; Beauchamp, Jacinthe; Gallant, François; Boucher, Anika; Chevarie, Jean-Sébastien; DeGrâce, Sara; Saheb, Yanis; Gagnon, Maryse; Doré, Isabelle; Sabiston, Catherine M. (Frontiers in Sports and Active Living, 2024)
Introduction We aimed to better understand longitudinal physical activity experiences among initially active adolescents and to identify and describe distinct physical activity profiles. Methods A sample of 23 physically active participants [52% female; mean age = 12.2 (0.6) years at study inception] were selected from the MATCH study to take part in this nested qualitative descriptive study. Participants were interviewed once a year for six years. Following individual-level analyses, profiles were identified based on similarity of longitudinal experiences. Results Four profiles captured participants' experiences: Independents (those who progressively seek activities that cater to their pursuit of autonomy); Multitaskers (those who participate in many different sports as an integral part of their lifestyle); Specialists (those who are dedicated to becoming the best they can be at one sport); Undecided (those who take part in physical activity to occupy time). Discussion The exploration of longitudinal physical activity experiences led to the identification of distinct profiles that could be targets for tailored interventions, theory development, and participation models.